Pengaruh Motivasi Kerja, Stress Kerja dan Konflik Kerja terhadap Kinerja Karyawan PT Assalaam Niaga Utama - Vikky Setiawan; Asih Handayani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the influence of human resources on employee performance. This study uses a quantitative method using primary data obtained from a questionnaire. The population in this study is PT Assalaam Niaga Utama. Determination of the research sample using the purposive sampling method and obtained a research sample of 105 respondents. Data analysis using the IBM SPSS statistic 23 program. For data analysis methods in this study are descriptive tests, data quality tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. The results of this study indicate that partially the variables of work stress and work conflict do not have a significant effect, while the variable of work motivation has a significant effect on employee performance.